2015
DOI: 10.1007/s00264-015-2930-4
|View full text |Cite
|
Sign up to set email alerts
|

Synovial haemangioma of the knee: an under recognised condition

Abstract: Synovial haemangioma is a rare but treatable condition. It should remain a differential for any patient with recurrent knee-joint symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Hemangioma is a commonly used misnomer for venous malformations in many vascular anomaly publications [15,16] and was also presented as an initial diagnosis among some of our cases. Also, intra-articular venous malformations of the knee may be misleadingly designated as synovial hemangiomas in the literature [17][18][19][20]. On MRI, hemangiomas are solid lesions with uniformly high signal intensity in T2-weighted sequences, prominent feeding arteries and draining veins, and intense and homogeneous enhancement after gadolinium.…”
Section: Discussionmentioning
confidence: 99%
“…Hemangioma is a commonly used misnomer for venous malformations in many vascular anomaly publications [15,16] and was also presented as an initial diagnosis among some of our cases. Also, intra-articular venous malformations of the knee may be misleadingly designated as synovial hemangiomas in the literature [17][18][19][20]. On MRI, hemangiomas are solid lesions with uniformly high signal intensity in T2-weighted sequences, prominent feeding arteries and draining veins, and intense and homogeneous enhancement after gadolinium.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical findings of synovial hemangioma are similar to those of D-TSGCT and hemophilic arthropathy. Both may cause sudden and non-traumatic intra-articular hemorrhage, and a delayed diagnosis can thus lead to osteoarthritis and joint function disuse ( 9 ). There are two case reports of synovial hemangioma in which >40 years passed from the onset of the disease until the final diagnosis ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that large venous synovial hemangiomas showed high signal intensity on T1-WI due to slow blood flow ( 20 ). Since synovial hemangiomas are blood-rich tumors and are usually heterogeneously enhanced on gadolinium contrast, the use of which helps distinguish these tumors from cystic synovial hyperplasia ( 23 ), intra-articular hematoma, and joint effusion ( 5 , 9 , 24 , 25 ). However, it has been claimed that synovial hemangioma was correctly diagnosed preoperatively in only 22% of cases ( 9 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our other three cases were local sessile intra-articular SH located near the superior pole of the patella, by far the most frequent location in the anterior compartment of the knee ( 5 8 , 19 , 21 , 24 , 27 29 , 38 , 40 , 42 , 44 , 50 , 53 57 ), followed by the infrapatellar fat pad ( 11 , 18 , 23 , 30 , 45 , 59 ), the posterior compartment, the medial compartment ( 2 – 4 , 25 , 35 , 39 , 42 , 54 , 61 ) and the intercondylar notch ( 22 , 43 , 46 , 47 , 54 ). The three reported patients with KSH near the superior pole of the patella had the rare phenomenon of bone erosion, which was localized in the patella in two cases, a previously undescribed location for KSH bone erosion, and in the supratrochlear cortical bone in one case.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is typically in the anterior aspect of the knee but can be posterior ( 14 ) or diffuse. Swelling, tenderness, effusion ( 5 , 9 11 , 17 , 21 , 23 , 26 , 30 , 33 , 34 , 44 , 49 , 50 , 55 ) and haemarthrosis ( 5 , 9 , 11 , 12 , 18 , 22 , 30 , 31 , 37 , 39 , 41 , 46 , 50 , 54 , 55 , 57 , 59 ) are frequent and can be recurrent. Occasionally, a palpable soft tissue mass ( 3 , 4 , 10 , 44 , 46 , 55 , 61 ) can be noted.…”
Section: Discussionmentioning
confidence: 99%